Statistical survey of pitch angle anisotropy of relativistic electrons in the outer radiation belt and its variation with solar wind/geomagnetic activity - Chakraborty, Suman; Rae, Iain Jonathan; Killey, Shannon; Ojha, Biswajit; Watt, Clare E. J.; Potts, Charles; Irving, Eleanor; Elliott, Gina; Johnson, Katherine; Mohammed, Nathanial; Gupta, Tara; Slater, Thomas; et al. (Frontiers in Astronomy and Space Sciences, 2024)
IntroductionIn this study, we use 7 years (2012–2019) of pitch angle resolved electron flux measurements from Van Allen Probe-B spacecraft to study the variation of near-equatorial pitch angle distributions (PADs) of outer radiation belt (L ≥ 3) relativistic electrons (E ≥ 0.5 MeV) with different levels of geomagnetic activity.MethodsWe calculate a pitch angle anisotropy index (PAI) to categorize the PADs into three types: pancake, PAI ≥ 1.05; butterfly, PAI ≤ 0.95; and flattop, 0.95 < PAI < 1.05.Results and DiscussionOur statistical results show that L shells ≥ 5 are dominated by pancake PADs on the dayside (9 < MLT < 15), butterfly PADs on the nightside (21 < MLT < 3), and flattop PADs in the dawn (3 < MLT < 9) and dusk (15 < MLT < 21) sectors, across almost all relativistic energies. In the inner L shells, the pancake and flattop PADs exhibit dependence on both L-shell and energy, with the occurrence rate increasing with decreasing L and increasing energy. For the butterfly PADs, we discovered a second population of low-L butterflies that are present at almost all local times. When the variation of electron PAI is compared with solar wind dynamic pressure Pdyn and geomagnetic indices SYM-H and AL, Pdyn is found to be the dominant parameter in driving the outer radiation belt pitch angle anisotropy. During periods of enhanced Pdyn, pancake PADs on the dayside become more 90°-peaked, butterfly PADs on the nightside exhibit enhanced flux dips around 90° pitch angle along with an enhanced azimuthal and radial extent, and flattop PADs turn into either pancake or butterfly PADs.